1995
DOI: 10.1016/0014-5793(95)01408-x
|View full text |Cite
|
Sign up to set email alerts
|

The molecular motion of bacteriorhodopsin mutant D96N in the purple membrane

Abstract: We measured the flash-induced absorption anisotropies of mutant bacteriorhodopsin (bR), D96N, in the purple membrane suspension. The measured anisotropy decay at 410 nm differed from that at 570 nm. These wavelength-dependent anisotropies show that the motion of absorption dipole of non-excited bR is faster than that of M-intermediate. The motion of nonexcited bR is considered as the rotational motion of whole protein in the purple membrane. This fact suggests that the photo-excitation induces the conformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…The M intermediate was assigned by comparing the 13 C chemical shift value of 20- 13 C and 14- 13 C with those previously reported for the M-intermediate [ 31 , 37 ] ( Table S1 ). It has been reported that an N intermediate is not observed in D96N-BR, because the proton donor D96 is replaced by N96 [ 22 , 23 , 24 , 25 ]. Therefore, another peak was assigned to the L intermediate and the chemical shifts agree with previously reported values [ 31 ] ( Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The M intermediate was assigned by comparing the 13 C chemical shift value of 20- 13 C and 14- 13 C with those previously reported for the M-intermediate [ 31 , 37 ] ( Table S1 ). It has been reported that an N intermediate is not observed in D96N-BR, because the proton donor D96 is replaced by N96 [ 22 , 23 , 24 , 25 ]. Therefore, another peak was assigned to the L intermediate and the chemical shifts agree with previously reported values [ 31 ] ( Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the photoreaction cycle shown in Figure 1 B, the photoreaction L ↔ M refers to proton exchange between SB and Asp85, while M ↔ N refers to proton exchange between Asp96 and SB. Therefore, replacement of Asp96 with Asn96 (D96N-BR) prevents the accumulation of any intermediate subsequent to the M intermediates, such as the N and O intermediates, while retaining proton pump activity [ 22 , 23 , 24 , 25 ]. Thus, the half-lives of the M and L intermediates are significantly increased in the D96N-BR mutant.…”
Section: Introductionmentioning
confidence: 99%